Father of nations [videorecording (Blu-Ray)] - Horch, Nathan; Horch, Nathan; Ogum, Ed; MacPherson, Kyra (House Lights Media, 2024)
Many years after a catastrophic event has decimated society, humanity is on the verge of extinction. The last few people continue in search of life, struggling to survive as they confront their mortality and purpose in a dying world.